Glass waste as supplementary cementing materials: The effects of glass chemical composition. (January 2015) - Bignozzi, M.C.; Saccani, A.; Barbieri, L.; Lancellotti, I.
Highlights: Glass waste with different chemical composition is used as supplementary cementing materials. Detailed study of glass waste dissolution in alkaline environment. Effects of glass chemical composition on ASR/pozzolanic behavior. Difficult issues in recycling glass waste containing PbO have been highlighted. Abstract: Sustainable cements containing 25 wt% of different types of recycled glass have been investigated as a supplementary cementing material in order to highlight the role of glass chemical composition during the hardening process. Glass formers, stabilizers and modifiers regulate the glass dissolution in the alkaline environment during cement hydration. As a consequence, pozzolanic reaction and/or alkali–silica reaction are strictly related to the glass chemical composition. The mechanical and microstructure characterizations of mortar samples containing glass blended cements and un-reactive aggregates allow to determine which oxides in the glass have to be carefully monitored to avoid deleterious reactions.